2019
DOI: 10.1038/s41419-019-2089-9
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA-5692 inhibits the progression of hepatocellular carcinoma by sponging miR-328-5p to enhance DAB2IP expression

Abstract: Circular RNAs (circRNAs), one kind of noncoding RNAs, can interact with miRNA and transcription factors to regulate gene expression. However, little is known on which circRNA is crucial for the pathogenesis of hepatocellular carcinoma (HCC). CircRNA expression profile was analyzed by a microarray. Regulatory gene targets were predicted by bioinformatics analysis and validated by luciferase assay. Their expression was determined by qRT-PCR and Western blotting. DNA methylation was determined by methylation-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
136
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(141 citation statements)
references
References 42 publications
4
136
0
1
Order By: Relevance
“…The dual-luciferase assay confirmed the direct binding of TPTEP1 and miR-328-5p in NSCLC cells. Aberrant expression of miR-328-5p has been reported in several cancer types, and was negatively regulated by circRNA (circRNA-5692) and lncRNA (LINC00210) (47,49,50). Our data implied that TPTEP1 downregulation may contribute to the increase of miR-328-5p in NSCLC, indicating TPTEP1 as a novel regulator of miR-328-5p.…”
Section: Discussionsupporting
confidence: 51%
“…The dual-luciferase assay confirmed the direct binding of TPTEP1 and miR-328-5p in NSCLC cells. Aberrant expression of miR-328-5p has been reported in several cancer types, and was negatively regulated by circRNA (circRNA-5692) and lncRNA (LINC00210) (47,49,50). Our data implied that TPTEP1 downregulation may contribute to the increase of miR-328-5p in NSCLC, indicating TPTEP1 as a novel regulator of miR-328-5p.…”
Section: Discussionsupporting
confidence: 51%
“…Moreover, a regulatory mechanism was recognized that circRNA may modulate the promoter methylation degree of its regulatory gene, thereby further to regulate its transcriptional expression [48]. For example, it was reported that circRNA-5692 decreased the methylation levels of the promoter region of the DAB2IP gene, thereby to further upregulate the expression level of the DAB2IP gene [49]. Thus, in this study, we also investigated the methylation status of CDK19 gene promoter region in SHF stem cells with overexpression or knockdown of circRNA-1926 for revealing the possible methylation events.…”
Section: Circrna-1926 Promotes Cdk19 Expression Without Modulating Thmentioning
confidence: 99%
“…It is becoming increasingly evident that dysregulated circRNAs are involved in almost all types of cancers, such as hepatocellular carcinoma, bladder cancer, breast cancer, and lung cancer, the latter having the highest morbidity and mortality rates in the world [13][14][15][16][17][18] . As the most common pathological classification of lung cancer, lung adenocarcinoma, which is often asymptomatic in the early stages, causes~500,000 deaths each year 18 .…”
Section: Introductionmentioning
confidence: 99%